Anomàli (EAAE Annual Conference Proceedings, 2024)
Anomàli mirrors the symbiotic efficiency of an ant colony, embracing “less is enough” as a design strategy for responsible stewardship. We explore architecture that preserves our built fabric while safeguarding resources, environment and culture:Less addition, more subtraction (the role of the architect): Architects focus on reducing energy and material use within planetary boundaries. Buildings are valuable resources, prioritized for repurposing rather than demolition and expansion.Less permanent, more maintenance (a common built environment). Architecture embraces change, with adaptable, lightweight structures designed to return to the earth. Community participation in bio-based maintenance fosters resilience and deepens our connection to the built environment.Less property, more cooperation (a social contract): Sharing strengthens belonging and expands access to resources. Possessing less individually, we gain more through cooperation and care for all living beings.Less necessity, more contingency (an individual role): Rather than extracting endlessly, we prioritize preservation to ensure abundance for future generations, redefining our relationship with resources beyond mere utility.